Video-Based Tasks in Strengthening Speaking Skills of EFL College Students - Sebastianus Menggo; Agnetis Basir; Yustus Sentus Halum (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2022)
All teachers, including speaking instructors, should be able to select the proper interactive media for students' speaking practice. Video-assisted learning tasks in the speaking class have not been explored extensively, despite the reality that video-based tasks are an appropriate choice for students to enhance their speaking ability. This study sought to examine the Effect of video-based tasks on students' speaking skills. In this study, a quasi-experimental design was employed, and the speaking scoring rubric served as the research instrument. Both the experimental group and the control group were comprised of participants. Researchers gave pre-and post-tests to identify the impact of the video-based tasks technique on students' speaking skills. Using a simple random sampling technique, 56 students from the English study program in the first grade at Universitas Katolik Indonesia Santu Paulus Ruteng comprised the research sample; then, the data were analyzed by using a t-test with the assistance of the SPSS 24.0 program. The data analysis of the average student score in the experimental and control groups revealed that the experimental group's average score (80,29) was higher than the control group's average score (67,57). This result demonstrates the significant effects of video-based tasks in teaching speaking. The researchers concluded that video-based tasks were helpful for teaching speaking skills. Moreover, video-based tasks significantly impact students' ICT skills, learning independence, and self-evaluation development. The logical implication of this study's findings is that EFL teachers should use videos to teach English, particularly speaking skills, because it has been demonstrated to have a favorable effect on the respondents' speaking ability.